KEBIJAKAN MANAJEMEN KEPALA SEKOLAH TERHADAP PENINGKATAN DISIPLIN SISWA D PAUD AL-QURAN AL-BAYYINAH KELURAHAN GROGOL KECAMATAN LIMO KOTA DEPOK - Anisa Dwi Amelia; Yunus Yunus (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to determine the principal's management policies for improving student discipline at the Al-Qur'an Al-Bayyinah Early Childhood Education Center (PAUD) in Grogol Village, Limo District, Depok City. This study used a qualitative approach with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions, which are common stages in descriptive qualitative research. The results indicate that the principal's management policies play a significant role in improving student discipline. These policies are realized through the development of school regulations, the introduction of daily activities, teacher role models, consistent supervision, and good communication with parents. The implementation of these policies has resulted in improved time discipline, behavioral discipline, cleanliness discipline, and social discipline among students within the school environment. Based on the results of the study, it can be concluded that the principal's management policies at the Al-Qur'an Al-Bayyinah Early Childhood Education Center (PAUD) are quite effective in improving student discipline. This success is influenced by the principal's commitment, teacher cooperation, and parental support in fostering learning.